2020
DOI: 10.1101/2020.03.21.001149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A glucose-stimulated BOLD fMRI study of hypothalamic dysfunction in mice fed a high-fat and high-sucrose diet

Abstract: Running headline: Hypothalamic fMRI in diet-induced obese miceAbbreviations: AgRP, agouti-related peptide; AMPK, AMP-activated protein kinase; ARC, arcuate nucleus; BOLD, blood oxygen level-dependent; CART, cocaine and amphetamine regulated transcript; CREB, cAMP response element-binding protein; DMN, dorsomedial nucleus; fMRI, functional magnetic resonance imaging; FOV, field of view; LH, lateral hypothalamus; MC4R, melanocortin 4 receptor; NPY, neuropeptide Y; POMC, pro-opiomelanocortin; PVN, paraventricular… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Other studies have shown before that the chronic consumption of high fat diets leads to obesity and negatively affects brain function in terms of a worsen outcome after ischemic stroke 41 and that short-term high-fat and high-sucrose feeding impairs hypothalamic neuronal circuits, particularly in the arcuate, the ventromedial and the dorsomedial nucleus. 42 Visa versa, short-term exercise training effectively decreases insulin-stimulated brain glucose uptake in sedentary subjects with insulin resistance. 43…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown before that the chronic consumption of high fat diets leads to obesity and negatively affects brain function in terms of a worsen outcome after ischemic stroke 41 and that short-term high-fat and high-sucrose feeding impairs hypothalamic neuronal circuits, particularly in the arcuate, the ventromedial and the dorsomedial nucleus. 42 Visa versa, short-term exercise training effectively decreases insulin-stimulated brain glucose uptake in sedentary subjects with insulin resistance. 43…”
Section: Discussionmentioning
confidence: 99%
“…Mice were anaesthetized with isoflurane and quickly decapitated, and brains were dissected, frozen in N2 (l) and stored at -80 °C until further experiments. For immunofluorescence experiments, mice under isoflurane anaesthesia were sacrificed by cardiac perfusion with cold PBS and then cold phosphate-buffered formaldehyde (Histolab, Askim, Sweden), and brains were processed as detailed previously (22).…”
Section: Tissue Samplingmentioning
confidence: 99%